Drug-loaded liposome hydrogel system for ureteral stent : effect of liposome formulation method on drug release - Teo, Joshua Jie Quan (2018)
Upper Tract Urothelial Carcinoma (UTUC) is a urological disease in which the upper urinary tract of the upper ureter and the kidney has developed cancer. Current standard of care employs the use of Radical Nephroureterectomy (RNU) with excision of the bladder cuff. However, this does not always produce a successful outcome due to problems such as frequent drug distillation, invasive procedure and huge patient discomfort. Therefore, there is a pressing need for a solution that prevents invasive surgery, involves sustained drug release, improves quality of patient care and reduces the high medical costs. Furthermore, there are several challenges that needs to be overcome in the proposed solution namely the high impermeability of the urothelium and drug retention. Hence, it is vital for the proposed solution to address these challenges for it to be an effective drug delivery device. The proposed solution is a drug-loaded liposome hydrogel ureteral stent that is implanted into the patient. In this project, the objective is to investigate the drug release behaviour affected by the hydrogel mesh size and liposome size for a drug-encapsulated liposome hydrogel. Characterization tools are carried out to study into the drug release behaviour. The findings can help in future research work where a better understanding of the drug release mechanism can help formulate an effective drug delivery system for applications. Following the completion of the project, the key findings found that 10% w/v 8K PEGDA hydrogels was most suitable hydrogel for the intended application. This conclusion was drawn based on the characterization study of hydrogel with 10% PEGDA concentration gels showing optimal hydrogel functionality of slow degradation and good physical and mechanical properties. Finally, based on preliminary studies, it has been established that a successful fabrication of a paclitaxel-encapsulated liposome hydrogel is feasible. For future research work, more emphasis can be placed into the translation from in- vitro study to in-vivo study. This would encourage the shift towards applications for different medical fields.s